Efektivitas Penerapan Sistem Keuangan Desa dan Kualitas Laporan Keuangan Desa - Gayatri, Gayatri; Latrini, Made Yenni (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 2 (2018)DO - 10.24843/JIAB.2018.v13.i02.p05, 2018)
This study aims to determine the effectiveness of the application of SISKEUDES to the quality of financial statements of village funds. The management of village funds becomes very important as part of the accountability practices since the funds provided by the government has increased each year. The SISKEUDES application is used to facilitate the administration of village funds financial statement. Implementation of SISKEUDES application will accelerate the completion of village funds financial statement accurately and timely. The population in this research is 46 villages of Badung regency receiving village funds which 30 villages were selected as the sample of this study. Finally, 18 villages with 73 respondents participated to answer the questionnaire given. Data collection was done by distributing questionnaires and simple linear regression used in analysing the data.This study proved that the application of SISKEUDES is effective on the quality of village funds financial statements in Badung regency. Keywords: SISKEUDES quality of financial statement, village funds